Development of a candidate reference material for adventitious virus detection in vaccine and biologicals manufacturing by deep sequencing. Issue 17 (12th April 2016) - Mee, Edward T.; Preston, Mark D.; Minor, Philip D.; Schepelmann, Silke; ,; Huang, Xuening; Nguyen, Jenny; Wall, David; Hargrove, Stacey; Fu, Thomas; Xu, George; Li, Li; et al.
Highlights: Deep sequencing has potential as an improved adventitious virus screening method. 15 laboratories sequenced a common reagent containing 25 target viruses. 6 viruses were detected by all lab, the remainder were detected by 4–14 labs. A wide range of sample preparation and bioinformatics methods is currently used. A common reference material is essential to enable results to be compared. Abstract: Background: Unbiased deep sequencing offers the potential for improved adventitious virus screening in vaccines and biotherapeutics. Successful implementation of such assays will require appropriate control materials to confirm assay performance and sensitivity. Methods: A common reference material containing 25 target viruses was produced and 16 laboratories were invited to process it using their preferred adventitious virus detection assay. Results: Fifteen laboratories returned results, obtained using a wide range of wet-lab and informatics methods. Six of 25 target viruses were detected by all laboratories, with the remaining viruses detected by 4–14 laboratories. Six non-target viruses were detected by three or more laboratories. Conclusion: The study demonstrated that a wide range of methods are currently used for adventitious virus detection screening in biological products by deep sequencing and that they can yield significantly different results. This underscores the need for common reference materials to ensure satisfactory assay performance and enable comparisons between laboratories.